1271. Prevalence and Factors Associated With HIV Testing Among Sexually Experienced 18–49-Year-Old Hong Kong Residents. (26th November 2018) - Zhao, Yanping; Parish, William; Yang, Li-Gang; Emch, Michael; Ho, King Man; Fong, Francois Yeung; Miu, Heidi Yin Hai; Tucker, Joseph D; Wong, William Chi Wai
Abstract: Background: The main HIV transmission route in Hong Kong is sex, accounting for 78.0% of the total reported cases. The majority of HIV cases were identified among those 20 to 49 years of age. In this study, we explored the prevalence and factors associated with HIV testing among 18 to 49 years old residents in Hong Kong. Methods: A population-based survey on sexual practice and health behavior was conducted in Hong Kong with a sample of 881 participants drawn from geospatial modeling, proportional to the district population sizes. Invitation letters were sent to selected households and interviewers were sent to recruit one subject per household. Once recruited, face-to-face interviews were carried out with a computer-assisted self-interview. The final data were weighted according to the 2011 Hong Kong census and factors identified through logistic regression. Results: Among 881 participants, 81.6% reported having sex before, among whom, 19.5% (137) had ever taken HIV tests. The main reasons for the 75.5% of participants not taking HIV testing are they do not think they are at risk of HIV infection (59.1%) or think they are very healthy (29.4%). The main places for HIV testing among those tested were public hospital/clinic (39.7%), private clinic/hospital (34.7%), and another 22.0% was tested in antenatal check-up or Hong Kong Red Cross. Among the sexually experienced residents, factors associated with HIV testing include marital status and number of sexual partners. Compared with single participants, those cohabiting, married, or with marital history were about seven times more likely to be tested (aOR = 6.73, 95% CI 2.23–20.31). Those who had >1 sexual partners were about twice as likely to be tested (aOR = 1.84, 95% CI 1.05–3.25). Other factors such as condom use, sexual orientation, anal sex behaviors or sexually transmitted infections history were not associated with HIV testing. Conclusion: HIV testing among Hong Kong residents is comparatively low. Though those with more than one sexual partner are more likely to be tested, those single, nonconsistent condom users, or with risky behavior such as anal sex behaviors do not associate with higher HIV testing. More HIV testing campaign and awareness raising shall be targeted toward people with at-risk behaviors. Disclosures: All authors: No reported disclosures.